Pragmatic Usage in Academic Email Requests: Comparing Written DCT and Email Data - Xuewei Chen (Lingue e Linguaggi, 2015)
Abstract - This project investigated the authenticity of written DCT with request emails from students to faculty. The researchers collected 52 emails from 12 Chinese graduate students majoring in Engineering at a southwest university at the United States and categorized them into five settings (appointment, committee, registration, signature and updates). These 12 participants also took the written DCT that was designed by the researchers based on the real email data. This article compared the outcomes from the real email data and the written DCT in term of length, supportive moves, request perspective and request strategies. The results showed that participants produced longer request in real email than in written DCT. There was no significant difference between real email data and written DCT in terms of grounder and request perspective.